Multi-scenario simulation and prediction of carbon surplus and deficit under the background of carbon neutrality: a case study of Chang-Zhu-Tan metropolitan area in China - Weiyi Sun; Jiaxi Liu; Xianzhao Liu; Tianhao Wang (Carbon Balance and Management)
Abstract Background Global climate change, marked by persistent warming trends, has emerged as one of the foremost challenges confronting human society in the 21st century. Systematically promoting carbon peak and neutrality has become a critical priority for governments in China. As the most active urbanization region in the country, metropolitan areas assume a pivotal leadership and exemplary role in executing carbon peak and neutrality initiatives. Consequently, we focus our research on the Chang-Zhu-Tan Metropolitan Area (CMA). The STIRPAT and CA-Markov models are employed to forecast carbon sinks and carbon emissions under various scenarios in 2030 and 2060, respectively, to explore pathways to carbon neutrality under various conditions. Results The findings indicate that the carbon surplus and deficit (CSD) values have consistently been negative from 2000 to 2020, signifying a persistent carbon deficit in the region, which has exhibited an upward trend. Notably, the CSD in Yuelu, Ningxiang, and Changsha experienced the most significant increases, particularly in Yuelu, where it reached − 11.22 × 106 t by 2020. Depending on the combinations of scenarios, the CSD values are anticipated to range from − 130.75 × 106 t to − 98.22 × 106 t in 2030, and from − 63.28 × 106 t to − 21.22 × 106 t in 2060. Furthermore, the carbon emissions under different scenarios are projected to reach peaks in 2030, with a maximum of 66.54 × 106 t in 2060. Conclusions The prediction results of carbon neutrality in the CMA indicate that carbon emission is expected to reach peaks before 2030 across various scenarios. However, carbon emissions will significantly exceed the carbon sink capacity by 2060, and there is still a carbon emission gap of at least 2122.44 × 104 t from achieving carbon neutrality, highlighting the necessity of accelerating emission reduction in the industrial and energy sectors. Consequently, the critical challenge to achieve carbon neutrality lies in the substantial reduction of carbon emissions.